Hydrothermalism and Deep-Water Ecosystems in the Atlantic Ocean - Cruise No. MSM06 - December 2007 - March 2008 - Portimão (Portugal) - Portimão (Portugal) - Toulon (France ) - Recife (Brazil) - Recife (Brazil) - Dakar (Senegal) - Hebbeln, Dierk; Petersen, Sven; Devey, Colin (DFG-Senatskommission für Ozeanographie, 2012)
Originally, RV MARIA S. MERIAN cruise MSM06 was planned to comprise three legs, all aiming at investigating hydrothermalism and/or deep-sea ecosystems in the Atlantic Ocean. However, due to technical problems the vessel was not available for these expeditions. Fortunately, it was possible to re-schedule all three cruises to other vessels, although with some reductions in the available ship time. The expedition planned as MSM 06-1 was finally conducted on the Dutch RV PELAGIA. It concentrated on cold-water coral ecosystems in the wider Gulf of Cadiz. The major aim of this leg was to detect the main forcing factors driving the distribution of cold-water corals and to investigate how these ecosystems developed under changing environmental conditions in the past. The other two expeditions were rescheduled to the French RV L´ATALANTE. Ex-MSM 06-2 focused on the Logatchev hydrothermal field at the Mid-Atlantic Ridge in the western North Atlantic, where a locally focused study was conducted to explore the causes for temporal and spatial compositional differences of hydrothermal fluids and their effect on the vent communities in this vent field. Ex-MSM 06-3 concentrated on another section of the Mid-Atlantic Ridge further to the east and just south of the equator. There, several topics related to the influences of large scale magmatic and tectonic processes on hydrothermal systems have been investigated. To achieve the ambiguous set-out goals, especially the very detailed investigation of sea floor settings inevitable to reach these goals, all three legs employed a remotely operated vehicle (ROV) as the main scientific instrument. This underlines how new technologies enable scientific work on a hitherto unmatched level of detail. Ex-MSM06-1 (RV PELAGIA cruise 64PE284): The focus of this expedition was on the investigation of cold-water coral ecosystems in the Gulf of Cádiz. For this expedition that contributed to the HERMES project (Hotspot Ecosystem Research on the Margins of the European Seas), an integrated project funded within the 6th FRP of the European Union, RV PELAGIA left Portimão at the Algarve coast on February 18, 2008. Equipped with the ROV CHEROKEE, a hopper camera and a TV-guided box corer, some mud volcanoes and mainly small sized carbonate mounds along the Spanish and Moroccan continental margins have been investigated. Although occasional findings of living cold-water corals have been made, as expected the majority of all coldwater corals encountered in the study area is composed of fossil material. However, the frequent occurrence of fossil corals, especially on the numerous small carbonate mounds at the Moroccan margin, clearly indicates that this region has been a preferred cold-water coral habitat in the past - probably under glacial conditions. After spending some final days at the Coral Patch Seamount, RV PELAGIA returned to Portimão on March 8, 2009. Ex-MSM06-2 (RV L´ATALANTE cruise HYDROMAR V): The overall goal of this expedition - to be conducted under the auspices of the DFG SPP 1144 - was the investigation of causes for temporal and spatial compositional differences of hydrothermal fluids and their effect on the vent communities in the Logatchev hydrothermal field. To achieve this goal, the Logatchev field located at the Mid- Atlantic Ridge at 14°45’N/45°W has been visited annually since 2004 (cruises M60/3, M64/2, MSM04/3). Thus, this expedition with RV L´ATALANTE was a continuation of the work done during the previous HYDROMAR expeditions. Unfortunately, the available working time at the site was finally reduced to 9 days, thus, allowing only a reduced work programme. Leaving from Toulon, France, the vessel reached the working area on December 16. The next day the first scientific dive of the ROV Kiel 6000 was carried out followed by seven further successful dives. Several instruments (seismometers, ocean bottom tiltmeter, ocean bottom accelerometer, high-temperature monitoring recorders) have been deployed at Logatchev for long-term measurements to facilitate relating changes in hydrothermal activity and vent exit temperature to tectonic processes. The hydrothermal plumes as well as low- and high temperature hydrothermal fluids have been sampled successfully, showing a pronounced increase in vent fluid temperatures when compared to earlier years. Ex-MSM06-3 (RV L´ATALANTE cruise MARSUED IV): This cruise also contributed to DFG SPP 1144 whose aim is to investigate the influences of large-scale magmatic and tectonic processes on hydrothermal and biological systems at spreading zones and to provide an estimate, valid on a regional to global scale, of the relative importance of the processes linking these parts of the systems. After leaving Recife, Brazil, on January 7, 2008, this cruise with RV L´ATALANTE had two major aims given the time available. Focusing on the MARSUED -Area (5°S, 12°W) in the central Atlantic these were: (a) Returning to observe and sample at the 4°48´S hydrothermal site (Turtle Pits etc.) which provided a wide variety of fluid types, habitats and geological settings to investigate the linkages between magmatism, fluid circulation and ecosystems in the deep sea. (b) Observing and sampling the lower crust on the 5°S Inside Corner High as there is mounting evidence that the deep crust also plays an important role in hydrothermal circulation and that water in the deep crust can strongly influence magmatic processes. Using the ROV Kiel 6000 at hydrothermal vents at Turtle Pits, turbulent fluid emanations with temperatures of about 400°C, i.e. the highest temperature measured so far in fluids at the MAR, have been observed. After a successful completion of the work programme this cruise ended on January 31 in Dakar, Senegal. : MARIA S. MERIAN-Berichte